O050 A ten-year review of methodological trends and outcomes in riskreducing mastectomy and associated reconstruction at a tertiary referral centre. (22nd July 2022) - Aslam, A; Arshad, Z; Ahmed, A; Kazzazi, F; Benson, JR; Forouhi, P; Agrawal, A; Benyon, SL; Irwin, M; Malata, CM
Abstract: Introduction: Risk-reducing mastectomy (RRM) is the removal of breast tissue to substantially decrease the risk of developing breast cancer in individuals with higher breast cancer susceptibility due to strong family history or genetic mutations. This retrospective study evaluates cases of RRM, and subsequent reconstruction performed at a tertiary referral centre over the last decade, with emphasis on mastectomy and reconstructive trends. Methods: A retrospective review of all cases of RRM performed between January 2010 and January 2020, divided into two groups corresponding to the first half (group 1) and second half (group 2) of the decade was conducted. Data collected included demographics, genetic test results, family and personal history of breast cancer, co-morbidities, mastectomy type, reconstruction type, surgical histopathology findings and complications. Results: A total of 167 patients (group 1=76, group 2=91) underwent RRM, with a significant increase in cases of RRM despite negative genetic test results (p=0.047). The proportion of nipple sparing techniques for RRM compared to more traditional skin-sparing techniques. Concomitantly, post-RRM reconstruction has progressively become solely implant-based, to coincide with a rise in ADM usage. This is consistent with national trends towards fewer complex autologous procedures. Take-home message: Emergent trends in risk-reducing mastectomy and reconstructive techniques are occurring against a background of broadened indications for RRM and more frequent patient requests for RRM in the absence of any documented pathogenic gene mutation. As breast surgery continues to evolve, it is important to evaluate specific trends such as more conservative forms of mastectomy and novel techniques/devices for breast reconstruction to ensure optimal patient care and levels of satisfaction.